Light and thermal niches of ground-foraging Amazonian insectivorous birds - Stouffer, Philip C.; Amaral, Bruna R.; Rodrigues, Patricia Fernandes; Jirinec, Vitek (Ecology, 2022)
Insectivores of the tropical rainforest floor are consistently among the most vulnerable birds to forest clearing and fragmentation. Several hypotheses attempt to explain this pattern, including sensitivity to extreme microclimates found near forest borders, particularly brighter and warmer conditions. Importantly, this “microclimate hypothesis” has additional implications for intact forest under global climate change that could be evaluated through direct assessment of the light and temperature environment of terrestrial insectivores. In this study, we harness novel technology to directly quantify the light and thermal niches of 10 species of terrestrial insectivores in undisturbed Amazonian rainforest. Loggers placed on birds (N = 33) and their environment (N = 9) recorded nearly continuous microclimate data from 2017 to 2019, amassing >5 million measurements. We found that midday light intensity in tree fall gaps (~39,000 lux) was >40 times higher than at the ground level of forest interior (950 lux). Light intensity registered by sensors placed on birds averaged 17.4 (range 3.9–41.5) lux, with species using only 4.3% (0.9%–10.4%) of available light on the forest floor. Birds therefore selected very dark microhabitats—the light environment was >2200 times brighter in tree fall gaps. Bird thermal niche was a function of ambient temperature as well as body temperature, which averaged >40.5°C but varied among species. Forest floor temperature peaked daily at 27.0°C, whereas bird loggers averaged 35.1°C (34.5–35.7°C) at midday. The antpitta Myrmothera campanisona and the antthrush Formicarius colma used thermal conditions closest to their body temperatures, whereas leaftossers (Sclerurus spp.) and Myrmornis torquata occupied relatively cool microclimates. We found no general link between abundance trends and variation in species-specific light and thermal niches. However, all species occupied markedly dim and cool microclimates. Because such conditions are rare outside the interior of primary forest, these results support the microclimate hypothesis in disturbed landscapes. Moreover, strong avoidance of conditions that are becoming more common under climate change highlights the vulnerability of terrestrial insectivores even in the absence of disturbance and may be the reason for enigmatic declines in Amazonia and elsewhere. © 2022 The Ecological Society of America.
Keywords: Biological Dynamics of Forest Fragments Project; Bird declines